Why Don't Private Employers Use Risk Adjustment? Conference Overview - Jacob Glazer; Thomas G. McGuire (SAGE Publishing, 2001)
In spite of advice from some researchers, private employers do not use formal risk adjustment to pay health plans. A conference, "Private Employers and Risk Adjustment," was held in February 2000 to consider the meaning of employers' actions. This overview introduces the papers written for that conference.